2007
DOI: 10.1002/jhet.5570440210
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of pyrazolo‐annelated heterocyclic ring compounds such as pyrazolo[3,4‐b]pyridines and pyrazolo[4′,3′:5,6]‐pyrido[2,3‐d]pyrimidines

Abstract: A series of pyrazolo[3,4‐b]pyridines has been synthesized by Friedländer condensation of 5‐amino‐pyrazole‐4‐carbaldehyde 1 with active methylene compounds in basic medium. Pyrazolo[4′3′:5,6]pyrido‐[2,3‐d]pyrimidines have been synthesized from pyrazolo[3,4‐b]pyridines using substituted urea and acetic anhydride.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 29 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…In the earlier communication 23, 24, we have studied Friedländer condensation on 5‐aminopyrazole‐4‐carbaldehyde (orthoaminoaldehyde) with various active methylenes. Herein, we studied the annelation of pyridine ring onto quinoline nucleus by condensing 7 with benzoylacetonitriles.…”
Section: Resultsmentioning
confidence: 99%
“…In the earlier communication 23, 24, we have studied Friedländer condensation on 5‐aminopyrazole‐4‐carbaldehyde (orthoaminoaldehyde) with various active methylenes. Herein, we studied the annelation of pyridine ring onto quinoline nucleus by condensing 7 with benzoylacetonitriles.…”
Section: Resultsmentioning
confidence: 99%
“…Condensation of 5-amino-1H-pyrazole-4-carbaldehyde 11 with propiophenone 2j afforded 3-(4-aryl)-5methyl-6-phenyl-1H-pyrazolo [3,4-b]pyridine derivatives 12 57 . On the other hand, condensation of 5aminopyrazole-4-carbaldehydes 11 and unsymmetric dialkylketones 2f yielded a mixture of isomeric pyrazolo [3,4-b]pyridine derivatives 13 and 14 58 .…”
Section: Synthesis Of Fused Pyrazolesmentioning
confidence: 99%
“…Friedländer condensation of 5-amino-1H-pyrazole-4-carbaldehyde 11 with acetonitrile derivatives 2 in ethanol in the presence of a catalytic amount of piperidine yielded the corresponding pyrazolo [3,4-b]pyridine-5-carbonitriles 16 58,59 . 6-Aminopyrazolo [3,4-b]pyridines 18 were obtained by the condensation of 1 with the corresponding cyanomethyl derivatives 17 57,[59][60][61] (Scheme 6). Panda et al 62 reported that treatment of 5-amino-1H-pyrazole-4-carbaldehyde 11a and 11b with various active methylene compounds 17a-c in the presence of an excess of sodium methoxide heated at reflux in methanol gave the corresponding pyrazolo [3,4-b]pyridines 7a-f (Scheme 7).…”
Section: Synthesis Of Fused Pyrazolesmentioning
confidence: 99%
“…However, both established methods were suffered from disadvantages of low yield, tedious workup, and requirement of low temperature below −5°C for the latter method. In continuation of our recent work aiming at the synthesis of various new pyrazole derivatives , we report a new method for the synthesis of ethyl 5‐amino‐4‐cyano‐1‐phenyl‐1 H ‐pyrazole‐3‐carboxylate 5 and novel pyrazolopyrimidine, N ‐alkylated pyrazolo[3,4‐ d ]pyridazin‐7‐one, and 3‐(hydrazinylcarbonyl)pyrazole‐4‐carboxamide derivatives, which have been tested for their antimicrobial activity.…”
Section: Introductionmentioning
confidence: 99%